Kinetics of human immunodeficiency virus type 1 (HIV-1) DNA and RNA synthesis during primary HIV-1 infection. - Graziosi, C (1993)
HIV-1 replication and viral burden in peripheral blood mononuclear cells (PBMC) have been reported to be high in primary infection but generally very low during the prolonged period of clinical latency. It is uncertain precisely when this transition occurs during the HIV-1 infection and what the relationship is between the changes in HIV-1 replication versus the clearance of infected cells in the overall control of viral replication. In the present study, the kinetics of viral burden (i.e., frequency of HIV-1-infected cells) and replication during primary and early-chronic infection were analyzed in PBMC of four acutely infected individuals. High frequencies of HIV-1-infected cells and high levels of virus replication were observed in PBMC after primary HIV-1 infection. Down-regulation of virus replication in PBMC was observed in all four patients coincident with the emergence of HIV-1-specific immune responses. Other parameters of virus replication, such as circulating plasma p24 antigen and plasma viremia showed similar kinetics. In contrast, a significant decline in viral burden in PBMC was observed in only one of four patients. These results indicate that the down-regulation in the levels of virus replication associated with the clinical transition from acute to chronic infection does not necessarily reflect a reduction in viral burden, thus suggesting the involvement of additional factors. Identification of these factors will be important in elucidating the host mechanisms involved in the early control of HIV-1 infection and disease.